Corporate Governance and Financial Performance of Nepalese Commercial Banks - Sapkota, Mohan Prasad (PYC Nepal Journal of Management, 2020)
This paper focuses on determining the relationship between corporate governance and financial performance of Nepalese commercial banks as well as examining the impact of corporate governance on banks performance. The sample consists of 9 commercial banks for the 10 year period of 2008/09 to 2017/18. Corporate governance is considered as leverage ratio, board meeting, board size and ownership concentration had mixed results on banks performance measured by ROE. Evidence indicates that debt ratio, net interest margin and total assets have significant positive contribution on banks performance. Board meeting and liquidity have negative impact on banks performance. However, board size and ownership concentration have no significant contribution to the firm performance.